2016
DOI: 10.1111/ppa.12613
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and occurrence of the carrot pathogen ‘Candidatus Liberibacter solanacearum’ haplotype C in Finland

Abstract: Occurrence of 'Candidatus Liberibacter solanacearum' (CLso) was studied in field-grown carrots (Daucus carota) in different regions of Finland. In addition, the frequency of CLso in carrots and in field populations of its vector, the carrot psyllid (Trioza apicalis), was studied in southwestern Finland. CLso was detected in six of the seven regions where the main carrot cultivation areas are located. The highest disease incidence was found in southwestern Finland, in the area where this carrot pathogen was ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…In Europe, CLso has not been associated with diseases in solanaceous plants, but with diseases in apiaceous plants, carrot and celery (Alfaro-Fernández et al 2012;Munyaneza et al 2010aMunyaneza et al , 2010bTeresani et al 2014). In Finland CLso was repeatedly detected in both the carrot psyllids (Trioza apicalis Förster) and the psyllid-infested symptomatic carrots (Haapalainen et al 2017;Munyaneza et al 2010aMunyaneza et al , 2010bNissinen et al 2014). Greenhouse experiments confirmed that the carrot psyllids transmit this bacterium and that the carrot leaf discolouration symptom is associated with a heavy CLso colonization in the plants (Nissinen et al 2014).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In Europe, CLso has not been associated with diseases in solanaceous plants, but with diseases in apiaceous plants, carrot and celery (Alfaro-Fernández et al 2012;Munyaneza et al 2010aMunyaneza et al , 2010bTeresani et al 2014). In Finland CLso was repeatedly detected in both the carrot psyllids (Trioza apicalis Förster) and the psyllid-infested symptomatic carrots (Haapalainen et al 2017;Munyaneza et al 2010aMunyaneza et al , 2010bNissinen et al 2014). Greenhouse experiments confirmed that the carrot psyllids transmit this bacterium and that the carrot leaf discolouration symptom is associated with a heavy CLso colonization in the plants (Nissinen et al 2014).…”
Section: Introductionmentioning
confidence: 93%
“…The CLso haplotype in the positive field potato samples was subsequently determined by PCR with primers LpFrag4-1611F and LpFrag4-480R (Table 1), amplifying a fragment of 16S-23S rRNA intergenic spacer and the 23S rRNA gene, and with primers CL514F and CL514R (Table 1), amplifying the 50S ribosomal protein rplJ/rplL gene region. The PCR reactions, agarose gel electrophoresis and purification of PCR products for sequencing were performed as previously reported (Haapalainen et al 2017). The DNA samples from the transmission experiments using grafting and dodder-bridging were also tested by nested PCR to detect CLso at a low titre.…”
Section: Detection and Quantification Of Clso By Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…For Lso, few studies have been attempted to investigate its population structure and genetic diversity, in particular due to its fastidious nature (Lin and Gudmestad, 2013). Sequencing of the 16S rRNA, 16S/23S ISR and 50S rpIJ - rpIL ribosomal gene loci has become the method of choice for the study of the genetic diversity of the bacterium (Lin et al, 2009; Wen et al, 2009; Nelson et al, 2011, 2013; Teresani et al, 2014; Alfaro-Fernández et al, 2017; Haapalainen et al, 2017; Hajri et al, 2017; Monger and Jeffries, 2018). However, genetic variation within these genes does not generally allow differentiation of closely related strains due to their high degree of conservation (Lin and Gudmestad, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports did not observe leaf discolouration associated with carrot psyllid damage (Markkula et al, ; Rygg, ), but Nissinen, Vanhala, Holopainen, and Tiilikkala () noted a later developing discolouration suggesting that a pathogen is associated with the psyllid damage. Recently, psyllids and affected carrots were found to be associated with the bacterium “ Candidatus Liberibacter solanacearum”, which has been documented from several countries (Haapalainen et al, ; Munyaneza et al, , ). However, the psyllid feeding symptoms are distinct from those caused by the bacterium (Nissinen, Haapalainen, Jauhiainen, Lindman, & Pirhonen, ).…”
Section: Introductionmentioning
confidence: 99%